Human factor, justice and organizational effectiveness in Africa - Acquaah, Moses; Tukamushaba, Eddy K. (Journal of Managerial Psychology, 2015)
The purpose of this paper is to examine the effect of the human factor (HF), organizational justice and the interaction between the two on individual employees’ perceptions of the effectiveness with which their organizations undertake activities in two sub-Saharan African countries. Design/methodology/approach – Survey data were collected from two samples containing public sector and private sector organizations from two sub-Saharan African economies – Ghana (n¼158) and Uganda (n¼208). Hierarchical regression analysis was utilized to analyze the survey data from the two countries separately. Findings – The HF dimensions of moral capital and human capabilities, and organizational justice were related to individual employees’ perceptions of the effectiveness of their organizations in both studies. In particular, higher perceptions of organizational justice at the workplace enhanced the impact of the HF dimensions of moral capital and human capabilities on individual employees’ perceptions of the effectiveness with which their organizations perform activities. Practical implications – Organizations in sub-Saharan Africa should emphasize the development of the HF qualities that focus on moral capital and the utilization and application of the knowledge, skills and abilities embedded in employees at the workplace. In particular, moral capital could play a critical role in ameliorating counter-productive attitudes and behaviors such as shirking, bribery and corruption in organizations. Moreover organizations in sub-Saharan Africa can improve their effectiveness by developing fair decision-making procedures and interactions between management/ supervisors and subordinates. Originality/value – The study provides the first empirical investigation of the link between the HF and perceived effectiveness of organizations, and how organizational justice moderates this relationship in a sub-Saharan African environment
Keywords: Competences; Employee behaviour; Organizational justice